Assessing Molecular Point-of-Care Testing and Dried Blood Spot for Hepatitis C Virus Screening in People Who Inject Drugs. (26th May 2020) - Chevaliez, Stéphane; Wlassow, Mélanie; Volant, Johann; Roudot-Thoraval, Françoise; Bachelard, Antoine; Poiteau, Lila; Trabut, Jean-Baptiste; Hézode, Christophe; Bourdel, Anne; Dominguez, Stéphanie
Abstract: Background: Injecting drug use is a major driver of hepatitis C virus (HCV) spread worldwide, and the World Health Organization (WHO) has identified people who inject drugs (PWID) as a key population to target for HCV screening and care. Point-of-care (POC) hepatitis C tests and dried blood spot (DBS) sampling offer benefits for the management of patients with HCV infection by increasing HCV testing and linkage to care in different nonclinical settings. The aims of this prospective study were to evaluate the feasibility and the acceptability of use HCV ribonucleic acid (RNA) POC and fingerstick DBS testing in social-medical risk-reduction centers and to describe the cascade of care among PWID in France. Methods: Between June 2018 and February 2019, 89 consecutive HCV-seropositive PWID attending 2 drug treatment services and 1 supervised consumption room in inner Paris were invited to participate in further evaluation, undergoing a clinical review with a liver assessment and blood tests including fingerstick capillary whole blood POC HCV RNA testing and fingerstick DBS sampling. Results: Of the 89 participants enrolled, HCV RNA was detected in 34 (38.6%) participants. Fingerstick whole blood POC RNA testing and HCV RNA detection from DBS sample were feasible and acceptable among PWID with no major difference in terms of HCV RNA detection rate. Overall, 16 participants received pan-genotypic antiviral treatment. The proportion of PWID with sustained virologic response at 12 weeks was 81.2%, with data for 3 patients still pending. Conclusions: One-step screening strategy based on the detection of HCV RNA would engage people in care for treatment scale-up and HCV elimination. Abstract : Injecting drug use is a major driver of hepatitis C virus spread worldwide. Point-of-care hepatitis C tests and dried blood spot (DBS) sampling are promising alternatives tools by increasing HCV testing and linkage to care in different non-clinical settings.